Tuesday

July 22, 2014

July 22, 2014

Posted by **tim** on Tuesday, May 31, 2011 at 4:56am.

- Math -
**Henry**, Wednesday, June 1, 2011 at 3:35pmY^2 = X(X-4)^2.

Let X = 0:

Y^2 = 0(0-4)^2 = 0,

Y = 0.

Let X = 1:

Y^2 = 1(1-4)^2 = 9,

Y = sqrt9 = +- 3.

(0,0),(1,+-3),(2,+-3.46),(3,+-1.73),

(4,0),(5,+-2.24).

Let X = -5:

Y^2 = -5(-5-4)^2 = -405,

Y=sqrt(-405) = sqrt(405*-1) =+- 20.1i.

(-5,+-20i),(-4,+-16i),(-3,+-12.1i),

(-2,+-8.49i),(-1,+-5i).

i = imaginary = sqrt(-1).

**Related Questions**

math pre calculus - find the following for the function f(x)=(x+5)^2(x-2)^2 a....

math - Graph x = y^2-6y+11 a. In function mode using two functions b. In ...

college algebra, Please help!! - Answer the following function. f(x)=2x^2-x-1 A...

college algebra, Please help!! - Answer the following function. f(x)=2x^2-x-1 A...

Math (repost) - Graph x = y^2-6y+11 a. In function mode using two functions b. ...

Math, please help - 1)Determine the equation of the polynomial function of ...

Math - Okay I have a scatterplot, so I have points on the graph. I need to use ...

Math - Given the function f(x)= x^2-3 / x+1, what point on the graph corresponds...

Algebra - Can someone pleas give me an example of a nonlinear function with 2 ...

Math - flickr.(dotcom)/photos/77304025@N07/6782789880/ Create a function that ...